Supportive Periodontal Treatment for the natural dentition and dental implants: a review (Mustansiria Dental Journal, 2022)
Aim: To assess the importance of successful periodontal treatment during long-term supportive periodontal treatment.The maintenance phase has been named the "cornerstone" of effective periodontal treatment when a patient is transferred from active treatment to a maintenance phase which is considered the final stage in comprehensive patient care, it takes effort and time from the patient, staff, and the dentist.Surgical and non-surgical techniques are used in periodontal therapy; patients should be put on a schedule of periodic reminder visits for supportive care once periodontal therapy is completed to avoid the recurrence of the disease. PD can recur due to poor mouth oral hygiene, insufficient subgingival removal, the microscopic nature of the dentogingival unit healing after periodontal treatment, and other factors. As a result, effective treatment should be provided to prevent disease recurrence.Conclusion: The success of periodontal therapy is based on a continuous schedule of periodontal maintenance therapy